INTERNATIONAL MIGRATION IN THE EUROPEAN CONTEXT - Stehlikova, Beata; Spirkova, Daniela (European Scientific Journal, ESJ, 2014)
The phenomenon of the international migration is an expression of intense globalization processes. Research has largely focused on objective determinants, as for example income of the international migration. Quality of life is equally important. It is undisputed, that democracy promotes quality of life and not every person perceives democracy the same way. MigrantsÂ´ quality of life is more a need of democracy which also needs multicultural environments. The aim of this paper is to answer the following question: What is the relationship between the subjective quality of life of the native, immigrants and democracy in the country? The answer we are looking for uses relevant support tools of quantitative methods - correlation and nonlinear regression analysis..